Antiviral Effectivity of Favipiravir Against Peste Des Petits Ruminants Virus Is Mediated by the JAK/STAT and PI3K/AKT Pathways - Zhang, Weifeng; Deng, Hualong; Liu, Yanfen; Chen, Shaohong; Liu, You; Zhao, Yuntao (Frontiers in Veterinary Science, 2021)
Peste des petits ruminants virus (PPRV), belonging to the genus Morbillivirus in the family Paramyxoviridae, causes severe infectious disease in small ruminants and has been rapidly spreading in many parts of Africa, the Middle East, and Asia. Although vaccination is considered to be an effective means of controlling PPR, the heat-sensitive nature of the vaccines against PPRV greatly limits their application in areas with a hot climate. In the present study, we investigated the anti-PPRV effects of favipiravir and sought to identify the underlying mechanisms in vitro using the Vero cell line. MTT assays, western blotting, indirect immunofluorescence assays, virus plaque formation assays, and qRT-PCR were used to assess the effects of favipiravir on the life cycle of PPRV and the expression of RNA-dependent RNA polymerase (RdRp). Additionally, the expression levels of JAK1, STAT1, phosphorylated (p)-STAT1, PI3K, AKT, and p-AKT, as well as those of signaling molecules acting downstream of the JAK/STAT and PI3K/AKT signaling pathways, were determined by western blot and qRT-PCR. The results indicated that, in PPRV-infected, favipiravir-treated Vero cells, the attachment, invasion, replication, and release of PPRV were significantly inhibited, as was the expression of RdRp, when compared with that in untreated PPRV-infected cells. Furthermore, in favipiravir-treated cells, the expression of JAK1 and STAT1 was downregulated, whereas that of p-STAT1 was significantly upregulated. Similarly, the expression levels of PKR, IRF9, ISG54, and MxA proteins that are associated with innate antiviral activity in host cells, were also markedly increased. Moreover, with favipiravir treatment, the expression of PI3K and p-AKT and the p-AKT/AKT ratio were significantly decreased, whereas the expression of AKT was noticeably upregulated. The expression of GSK3, NF-κB p65, p-NF-κB p65, and BAD was also increased with favipiravir treatment, while the expression of CREB, p-CREB, p-GSK3 and Bcl-2 was slightly decreased. In addition, all the p-GSK3/GSK3, p-CREB/CREB, p-NF-κB/NF-κB, and p-BAD/BAD ratios were significantly reduced in favipiravir-treated cells. These results implied that the antiviral effectivity of favipiravir against PPRV is mediated by the JAK/STAT and PI3K/AKT pathways and that favipiravir has potential for use as an effective antiviral agent against PPRV.